Mengungkap Faktor yang Memengaruhi Keputusan Gen Z dalam Menggunakan Uang Elektronik - Maulana Oktora, Idham; Primadhita, Yuridistya; Indiarti, Miralda; Jayadi, Jayadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
The study was conducted to identify the determinants of Generation Z's decision to utilize electronic money as a payment instrument. This study employed a quantitative approach with a survey method. The research sample included 95 respondents as the unit of analysis. Statistical analysis was conducted using SPSS version 25. The study yielded findings showing that perceived usefulness and perceived ease of use have a positive and significant influence on the extent of the decision to use electronic money. These findings illustrate that perceived usefulness and perceived ease of use are important determinants influencing Generation Z to adopt digital payment technology. Digital payment service providers need to improve functionality and ease of access to encourage wider adoption of electronic money.